XML Databases and the Semantic Web - Thuraisingham, Bhavani (CRC Press, 2009)
Efficient access to data, sharing data, extracting information from data, and making use of the information have become urgent needs for today's corporations. With so much data on the Web, managing it with conventional tools is becoming almost impossible. New tools and techniques are necessary to provide interoperability as well as warehousing between multiple data sources and systems, and to extract information from the databases. XML Databases and the Semantic Web focuses on critical and new Web technologies needed for organizations to carry out transactions on the Web, to understand how to use the Web effectively, and to exchange complex documents on the Web.